MANFAAT INVESTASI PEMBANGUNAN JALAN TOL BANDUNG INTRA URBAN DARI PERSPEKTIF MAKRO - P Pradono; Handini Pradhitasari (TATALOKA, 2011)
This article aims to assess the economic impact in a wider perspectives of the Bandung Intra Urban toll road project. Bandung Intra Urban Toll Road is a proposed project aimed at connecting the east and west corridor along the 27.273 km of Bandung. The feasibility study stated the project is feasible economically and financially. By using input-output method, this study aims to assess the economic benefits of this investment project, which includes linkages, multiplier to the impact of output, income and employment generation. The results showed that of 53 sectors in the city of Bandung, the communication service sector is the sector with the highest backward linkages. Meanwhile, the trade sector is the sector with the largest forward linkage. Multiplier effects are divided into type I and II. The sector which has the highest multiplier output type I is the communication sector (sector 42), whereas the highest multiplier output type II is the public education sector (sector 47). For the income multiplier, the sector with the highest multiplier type I and type II is the wooden industry (Sector 18) and sector which has the biggest employment multiplier is the financial sector. The investment value for the BIUTR project would generate the city’s economy through the impact of output, income and employment for its own sector, but has not given a significant impact on other sectors. In general, it can be concluded that the input-output method can give a wider economic benefits of an investment project of the highway.